2005
DOI: 10.1371/journal.pbio.0040009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NK Cells by an Endocytosed Receptor for Soluble HLA-G

Abstract: Signaling from endosomes is emerging as a mechanism by which selected receptors provide sustained signals distinct from those generated at the plasma membrane. The activity of natural killer (NK) cells, which are important effectors of innate immunity and regulators of adaptive immunity, is controlled primarily by receptors that are at the cell surface. Here we show that cytokine secretion by resting human NK cells is induced by soluble, but not solid-phase, antibodies to the killer cell immunoglobulin-like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
343
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(363 citation statements)
references
References 78 publications
(105 reference statements)
15
343
1
4
Order By: Relevance
“…It is interesting to note that KIR2DL4 that displays limited polymorphism, [27][28][29] and shares high structural homologies to KIR2DL5, binds to the conserved non-classical HLA-G molecule. 6,9 The known regulatory elements in the promoter region are conserved in all KIR2DL5 sequences. 13 Of the 21 distinct KIR2DL5 sequences, eight belong to 2DL5A and the remaining 13 belong to 2DL5B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting to note that KIR2DL4 that displays limited polymorphism, [27][28][29] and shares high structural homologies to KIR2DL5, binds to the conserved non-classical HLA-G molecule. 6,9 The known regulatory elements in the promoter region are conserved in all KIR2DL5 sequences. 13 Of the 21 distinct KIR2DL5 sequences, eight belong to 2DL5A and the remaining 13 belong to 2DL5B.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite clustering together into a discrete lineage with high structural homologies, the KIR2DL5 and 2DL4 differ substantially in their amino-acid sequences, genomic locations, population distributions, level of transcriptions, cellsurface expressions, ligand specificities and signaling functions. [5][6][7][8][9] The KIR2DL4 gene is present on most KIR haplotypes and occurs at a frequency of 100% in most populations, whereas KIR2DL5 is variable among KIR haplotypes and thus differs considerably between populations in its frequency. [10][11][12] Two copies of the KIR2DL5 genes have been characterized, KIR2DL5A and KIR2DL5B, that show 99.5-99.7% identity in their coding sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blastocyst, however, is well equipped to counteract this harmful situation. Synthesis of HLA-G as a substitute of missing HLA class I, allows blastocysts not only to silence uNK and CTL anti-blastocyst cytotoxicity, but also to obtain uNK cooperation for embryo development by inducing these cells to secrete embryotrophic cytokines and factors promoting cell growth, angiogenesis, and EVT survival and invasiveness (Rouass-Freis et al, 1997;Moretta and Moretta, 2004;Perham, 2004;Rajagopalan et al, 2006). In addition, the occurrence in uterus at blastocyst implanting time of a high number of protective molecules (Leukemia Inhibitory Factor, heme oxygenase HO-1, IL-10, TGF-, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Rajagopalan et al [33] have recently showed that sHLA-G, following binding to the CD158d receptor on the surface of human resting NK cells, is endocytosed and triggers the expression of a set of chemokines and cytokines driving a proinflammatory/proangiogenic response. These findings suggest that NK cells can exert beneficial effects at sites of HLA-G expression, such as stimulation of vascularization in the maternal decidua during pregnancy.…”
Section: Molecular and Functional Characteristics Of Shla-gmentioning
confidence: 99%